Fangirl down : a novel [compact disc, unabridged] - Bailey, Tessa (Bailey, Tessa. Big shots series., 2024)
Josephine Doyle believed in gorgeous, grumpy golfer Wells Whitaker even when he didn't believe in himself. Yet after he throws in the towel, she wonders if her faith was misplaced. Then a determined Wells shows up at her door with a wild proposal: be his new caddy, help him turn his game around, and split the prize money. As they travel together, sparks fly.